Cardiovascular and renal effects of novel nonpeptide nociceptin opioid peptide receptor agonists. (12th December 2021) - Denys, Ian B.; Gao, Juan; Sutphen, Jane C.; Zaveri, Nurulain T.; Kapusta, Daniel R.
Abstract : Background and Purpose: Partial agonists of the nociceptin opioid peptide (NOP) receptor have potential therapeutic use as antihypertensive and water diuretics (aquaretics). To date, peptide NOP receptor ligands have failed to progress in clinical trials due to poor pharmacokinetics and adverse effects. Nonpeptide, small‐molecule NOP receptor ligands may be more suitable as therapeutic agents. This study investigated the cardiovascular and renal responses produced by the novel nonpeptide NOP agonists AT‐403, AT‐090, AT‐127, and AT‐039. Experimental Approach: Changes in mean arterial pressure (MAP), heart rate (HR), renal excretory function and occurrence of sedation and hyperphagia were determined before and after i.v. bolus injection or infusion of the NOP agonists in conscious Sprague–Dawley rats. Additional studies involving (i) measurement of renal sympathetic nerve activity (RSNA) and (ii) renal denervation were conducted to investigate the role of the renal nerves in the cardiorenal responses to AT‐039. Key Results: Bolus i.v. injection of AT‐403, AT‐090, AT‐127 and AT‐039 produced significant decreases in MAP and HR and a sodium‐sparing diuresis. AT‐403, AT‐090, and AT‐127, but not AT‐039, induced sedation and hyperphagia at all doses tested. Infusion i.v. of AT‐039 produced hypotension and aquaresis without adverse central nervous system effects or change in HR, responses that were also observed in renal denervated rats. Conclusions and Implications: Nonpeptide NOP agonists decrease blood pressure and produce aquaresis in conscious rodents. Due to lack of sedation and hyperphagia, AT‐039 represents a novel NOP agonist that may be useful for treatment of hypertension and/or volume overload/hyponatraemic states.